2018
DOI: 10.1002/jlb.5ri0218-084r
|View full text |Cite
|
Sign up to set email alerts
|

Translational and clinical advances in JAK-STAT biology: The present and future of jakinibs

Abstract: In this era, it is axiomatic that cytokines have critical roles in cellular development and differentiation, immune homeostasis, and host defense. Equally, dysregulation of cytokines is known to contribute to diverse inflammatory and immune-mediated disorders. In fact, the past 20 years have witnessed the rapid translation of basic discoveries in cytokine biology to multiple successful biological agents (mAbs and recombinant fusion proteins) that target cytokines. These targeted therapies have not only fundame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
101
0
18

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(120 citation statements)
references
References 203 publications
(355 reference statements)
1
101
0
18
Order By: Relevance
“…Interestingly, GWAS performed on other, larger population samples for phenotypes other than TB have shown that homozygosity for TYK2 P1104A has a strong protective effect (ORs ranging from 0.1 to 0.3) against various autoinflammatory or autoimmune conditions (25,(48)(49)(50)(51)(52)(53)(54). In light of these results, the potential pharmacological benefits of TYK2 inhibitors for treating autoinflammatory or autoimmune conditions are currently being evaluated (55)(56)(57). Our findings indicate that if such treatments were to be introduced into widespread use, then it would be important to assess the risk of TB before and during treatment, as is currently done for anti-TNF immunotherapy (58).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, GWAS performed on other, larger population samples for phenotypes other than TB have shown that homozygosity for TYK2 P1104A has a strong protective effect (ORs ranging from 0.1 to 0.3) against various autoinflammatory or autoimmune conditions (25,(48)(49)(50)(51)(52)(53)(54). In light of these results, the potential pharmacological benefits of TYK2 inhibitors for treating autoinflammatory or autoimmune conditions are currently being evaluated (55)(56)(57). Our findings indicate that if such treatments were to be introduced into widespread use, then it would be important to assess the risk of TB before and during treatment, as is currently done for anti-TNF immunotherapy (58).…”
Section: Discussionmentioning
confidence: 99%
“…Histopathology was used to confirm imaging observations in the SKG experiments. In our hands, the onset of small intestine kinases (JAKs), are of particular interest given the large number of orally available small-molecule inhibitors developed recently (15). JAK inhibitors (JAKinibs) already are approved for clinical use in rheumatoid arthritis and PsA, and a recent proof-of-concept trial showed that the pan-JAK inhibitor tofacitinib provided both symptomatic control in AS and reduced axial joint inflammation on MRI (16).…”
Section: Introductionmentioning
confidence: 99%
“…Расширение представлений о роли оси ИЛ23/ИЛ17 в развитии ИВЗ послужило мощным стимулом для разработки генно-инженерных биологических препаратов (ГИБП) и «малых» молекул, блокирующих эффекты цитокинов оси ИЛ23/ИЛ17 или внутриклеточную сигнализацию этих цитокинов [10,[27][28][29], некоторые из которых уже широко применяются для лечения ИВЗ, а другие проходят стадию клинических или преклинических исследований (табл. 2).…”
unclassified
“…Большой интерес представляет возможность модуляции оси ИЛ23/ИЛ17 с использованием низкомолекулярных химически синтезированных препаратов (тофацитиниб, барицитиниб и др. ), ингибирующих внутриклеточные «сигнальные» молекулы -JAK (Янус-киназы), так называемые Якинибы (Jakinibs), которые с успехом применяются для лечения РА [27][28][29]. Теоретическим обоснованием их эффективности при псориазе, ПсА, АС и ВЗК является модуляция оси ИЛ23/ИЛ17 за счет блокирования JAK2-TYK2/STAT3-STAT4, JAK1-TYK2-STAT5, участвующих в сигнализации ИЛ12, ИЛ23, ИЛ21, ИЛ22 и, вероятно, других патогенетически значимых для каждого конкретного заболевания воспалительных медиаторов (ИЛ15, ИФНγ и др.)…”
unclassified